[Boxing ; Basil Valdez ; STL [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1988)
Deals with controversy of two Filipino boxers in a face-off to determine who will represent the country in the Seoul Olympics; the evils and benefits of small town lottery in the Philippines; and the interviews with top Filipinos balladeer about his philosophy in life.
Boxing (15 min.) -- Basil Valdez (12 min.) -- STL (12 min.)
VHS.
Keywords: Valdez, Basil; Amateur Boxing Association of the Philippines -- Corrupt practices; Boxing -- Philippines; Boxing -- Corrupt practices -- Philippines; Gambling -- Philippines; Lotteries -- Philippines